Mixed oligosaccharides-induced changes in bacterial assembly during cucumber (Cucumis sativus L.) growth - Wang, Qiushui; Zhou, Xin; Liu, Yue; Han, Yan; Zuo, Jia; Deng, Jie; Yuan, Liyan; Gao, Lijuan; Bai, Wenbo (Frontiers in Microbiology, 2023)
The application of oligosaccharides can promote plant growth by increasing photosynthesis or inducing plant innate immunity. However, the mechanisms by which oligosaccharides affect bacterial community diversity and abundance remain unclear. In this study, a mixed oligosaccharide was applied to the growth of cucumbers. The findings of the present study suggest that the application of MixOS has significant effects on the bacterial communities in the phyllosphere, rhizosphere, and bulk soil of cucumber plants.Illumina MiSeq sequencing was used to test the effects of mixed oligosaccharides on bacterial community composition and the bacterial co-occurrence network in the cucumber phyllosphere, rhizosphere, and bulk soil. The treatment with MixOS resulted in delayed senescence of leaves, well-developed roots, and higher fruit production. The bacterial diversity and composition varied among the different ecological niches, and MixOS application caused significant shifts in the bacterial microbiome composition, particularly in the phyllosphere.The results have shown Moreover,that mixed oligosaccharides increased the abundance of potential growth-promoting bacterial abundance ofsuch as Methylorubrum spp. and Lechevalieria spp., and more zOTUs were shared between the WM and MixOS treatmentsaltered the diversity of the bacterial community in the cucumber phyllosphere, rhizosphere, and bulk soil. In tFurthermore, the bacterial co-occurrence network analysis, suggested that the modularity of the phyllosphere networks was the highest among all samples. The bacterial co-occurrence networks were altered because of the application of MixOS, indicating a greater complexity of the bacterial interactions in the rhizosphere and bulk soil The application of mixed oligosaccharides decreased the modularity of all ecological niche samples. These results findingsprovide a theoretical basis for exploring the mechanisms by which suggest that mixed oligosaccharides has the potential to improve plant growth and yield by modulating the bacterial communities within and outside the plantspromote cucumber growth and could provide a theoretical basis for future agricultural production. guide future agricultural production.